Analisis Validitas dan Realibilitas Kualitas Soal Pilihan Ganda Asesmen Kompetensi Minimum (AKM) Mata Pelajaran Pendidikan Agama Islam Menggunakan Pendekatan Model Rasch - Azzahra, Nuri Syifa; Sumarni, Sri; Putranta, Himawan (IIQ An Nur Yogyakarta, 2024)
This journal article discussed validity and reliability analysis research in determining the quality of multiple choice questions of Minimum Competency Assessment (AKM) in Islamic Education subjects that focused on inheritance material in Islam using the Rasch approach model. This study aimed to explain the results of the analysis carried out descriptively by utilizing the QUEST program and using the content validity instrument sheet using Aiken'V formula. The multiple choice questions were ten in number, consisting of five literacy AKM questions and five numeracy AKM questions with five alternative answers which were then distributed to thirty student respondents. This type of research was quantitative research that used a descriptive study approach method. The results of the research analysis showed seven question items were appropriate and three question items were not appropriate and all items were valid.